Development of the Simplified Chinese version of neonatal palliative care attitude scale - Zhong, Yajing; Black, Beth Perry; Kain, Victoria J.; Sun, Xiaoming; Song, Yang (Frontiers in Pediatrics, 2022)
Background: The provision of palliative care for neonates who are not expected to survive has been slow in mainland China, and this model of care remains in its early stages. Evaluating nurses’ attitudes towards neonatal palliative care (NPC) has the potential to provide valuable insight into barriers impeding NPC implementation. This study aimed to translate and adapt the traditional Chinese version of the Neonatal Palliative Care Attitude Scale (NiPCAS) into simplified Chinese to assess its psychometric properties. Methods: The NiPCAS is a valid and reliable instrument to measure nurses’ attitudes for evidence-based practice. To date, the scale has not been used in mainland China. With cultural adaptation and pilot testing, the traditional Chinese version of the NiPCAS was translated into simplified Chinese. Its reliability was tested using internal consistency and test-retest reliability, and its validity was measured using the content validity index and exploratory factor analysis. Results: A total of 595 neonatal nurses from mainland China were recruited. Twenty-six items in the scale were translated into simplified Chinese. The scale demonstrated excellent reliability with a Cronbach’s α coefficient of .87 and a test-retest reliability of 0.88. To support the simplified Chinese version of NiPCAS, the scale content validity score was 0.98, and the exploratory factor analysis revealed five factors representing the conceptual dimensions of the scale. Conclusion: This study demonstrated the psychometric properties of the simplified Chinese version of NiPCAS, validated its use as a viable tool for measuring neonatal nurses' attitudes towards NPC, and identified facilitators and barriers to NPC adoption. Our findings suggested supported clinical application in the context of mainland China. A confirmatory factor-analysis approach with a different sample of neonatal nurses is required for further testing of the instrument in the future.